Transnational Activities and Identifications –A population-based study on three immigrant groups in Finland. (2nd September 2022) - Kemppainen, Laura; Kemppainen, Teemu; Rask, Shadia; Saukkonen, Pasi; Kuusio, Hannamaria
ABSTRACT: Our understanding of the lived experience of transnationalism is limited by the scarcity of high-quality quantitative evidence. Representative evidence on the emotional and identification aspects of transnationalism is especially missing. To address this gap, we investigated the transnational involvement of three migrant groups – Somali, Kurdish and Russian – in Finland. Using high-quality random sample survey data, the study examined transnational activities – remittance sending, following media, keeping in touch with and visits to the country of origin – as well as transnational identification with significant others living abroad. Multiple correspondence analysis (MCA) demonstrated that transnational involvement can be empirically divided into transnational activities and identifications, as suggested by prior theoretical works. Regression analysis showed that transnational activities and identifications varied strongly between the three groups. Russians were the most active in transnational activities while Somalis showed the highest levels of identification with their country of origin. Activities increased with the longer stay, while identification decreased. Family ties played a role in transnational identification. Our results point towards the complexity in the relationship between transnational involvement and economic integration in the host society.